Genetic Characterization of Cambodian Fasciola gigantica and Dispersal Direction of the Species in Asia - Vandara Loeurng (2019)
© 2019 Elsevier B.V. Fasciola gigantica and hybrid Fasciola are distributed throughout Asia. Herein, we investigated the species of the Fasciola fluke distributed in three hotspots of fascioliasis in Cambodia. A total of 92 flukes collected from 21 slaughtered cattle from Kandal (44), Battambang (41), and Kratie (7) Provinces were identified as F. gigantica using multiplex PCR for a nuclear phosphoenolpyruvate carboxykinase (PEPCK) gene. The overall prevalence of F. gigantica infestation was 7.14% (21/294). Phylogenetic as well as population genetics analyses were performed using the mitochondrial NADH dehydrogenase subunit 1 (ND1). The 19 ND1 haplotypes were identified from Cambodian F. gigantica (haplotype diversity, 0.83). All of the haplotypes were classified into F. gigantica haplogroup C, which includes ND1 haplotypes detected from Thailand, Vietnam, Indonesia, Myanmar, and China. Among haplogroup C, novel and unique haplotypes of Cambodia were found in the Battambang and Kandal Provinces, and the nucleotide diversity of the Cambodian population (0.00532) was the highest. Pairwise fixation indices among the F. gigantica populations from these countries indicated that the Cambodian and Thailand populations were related to each other. The highest genetic diversity in the Cambodian population suggests that F. gigantica in Cambodia may be the ancestor of the populations in Southeast Asian countries. Most likely, livestock movement, including Zebu cattle, played an important role in the transmission of F. gigantica. In this study, the hybrid Fasciola flukes that are commonly found in neighboring countries, were not found in Cambodia. Further comprehensive investigations of Fasciola prevalence should be conducted by analyzing a wider range of hosts throughout Cambodia to reach a more solid conclusion about the absence of hybrid flukes.